The Sadducees and the Water Libation - Rubenstein, Jeffrey (The Jewish quarterly review, 1994)
The consensus of scholarship believes that the Sadducees rejected the legitimacy of the Sukkot water libations. This conclusion is based on two principal arguments. The first argument rests on rabbinic traditions which supposedly state that the Sadducees opposed the libation. The second argument is based on the assumption that the Sadducees rejected "the Oral Law" which provided the authority for the ritual. Neither of these arguments stands up to criticism. Rabbinic sources nowhere state that the Sadducees rejected the libation. New evidence from Qumran, together with more methodologically aware analyses of rabbinic texts, have revised the general conception of the Sadducees and their approach to law. The libation controversy must therefore be explained on other grounds. Two possible explanations are proposed. The controversy may have derived from a dispute concerning the place upon the altar where libations should be poured. It is also possible that the controversy centered on the legitimacy of bringing the water libations on the Sabbath and not on the legitimacy of the libation per se.